Spatial distribution of the four invasive plants and their impact on natural communities’ dynamics across the arid and semi-arid environments in northwest Pakistan - Khan, Nasrullah; Ullah, Rafi; Okla, Mohammad K.; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Abu-Harirah, Hashem A.; AlRamadneh, Tareq Nayef; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Introduction Non-native species are globally successful invaders with negative impacts on vegetation communities’ social, economic, and ecological values. Hence, the current research was carried out to assess the spatial distribution patterns and vegetative diversity of the four non-native species in severely invaded areas of the semi-arid parts of northern Pakistan. Methods The research was conducted using data from 1065 plots spread across 165 sites. These sites represented habitats throughout Northern Province, such as farm countryside, highlands, and abandoned places in rural and urban areas. Results and discussion The communities were floristically diverse, represented by 107 plant species, and dominated mainly by annual and perennial life forms with herbaceous habits. Similarly, the floristic structure shows significant variation tested by the χ2 test (P< 0.05) for plant status, life forms, life cycle, and habitat base distribution. In addition, the diversity indices show significant variation having the highest diversity in C-III (P. hysterophorus-dominated sites) and lowest in C-IV (S. marianum-dominated sites, i.e., primarily pure communities), indicating non-native species may increase or decrease site diversity. The diversity communities were further supported by higher quantities of soil nutrients, i.e., organic percentage (2.22 ± 0.04). Altitude, soil nutrients, and texture were shown to be the environmental factors most associated with communities that non-native species had invaded. Recommendation It is recommended that relevant, additional soil and climatic parameters be integrated into species distribution models to improve our understanding of the ecological niches of different species and to make a collective approach for preserving and conserving native plant communities.